PENERAPAN SISTEM TEKNOLOGI KEUANGAN DI LPD SESETAN UNTUK MEMPERMUDAH AKSES MASYARAKAT - Ni Wayan Saba Astuti; I Ketut Westra; Ni Wayan Widi Astuti (Program Studi Pendidikan Ekonomi Universitas PGRI Mahadewa Indonesia, 2026)
The implementation of a financial technology system at the Sesetan Village Credit Institution (LPD) aims to improve operational efficiency and simplify public access to financial services. The technology applied includes the use of digital applications that allow the community to perform transactions quickly, securely, and conveniently. This system is expected to reduce manual errors, accelerate service processes, and provide ease for the public to access financial services anytime and anywhere. This research uses a qualitative approach, with data collection methods through interviews, observations, and literature review. The findings show that the implementation of financial technology at LPD Sesetan can increase public satisfaction, expand service reach, and have a positive impact on the sustainability of LPD operations